The frequencies of localized acoustic modes in Au/V nanolayers with capping layer - Aleksiejuk, M. (Archives of Acoustics, 2006)
Paper presents the results of theoretical analysis of localized acoustic modes, which can begenerated in Au/V nanolayers with “heavy” capping layer. The transfer-matrix method wasused to evaluate frequencies of localized acoustic modes in these nanostructures. Up to nowthe condition of generation of localized modes in nanolayer structure was that the acousticimpedance of capping layer is lower then the acoustic impedance of top (next) layer. Thiscondition was in agreement with experimental results. This paper demonstrates the possibilityof generation of localized acoustic modes in case of higher acoustic impedance of cappinglayer. The frequencies of localized modes for different thickness of capping layer were obtained.